Leveraging calcium-NOM complexation phenomenon as RO fouling mitigation strategy during treatment of lake water - Oranso T. Mahlangu; Samkeliso S. Ndzimandze; Mxolisi M. Motsa; Bhekie B. Mamba (Advanced Membranes)
Organic fouling during reverse osmosis (RO) is exacerbated by the presence of calcium up to a limit where extremely high calcium concentration results in lesser fouling due to formation of large organic-calcium aggregates with lower cake resistance. Therefore, this work leveraged on this phenomenon and used calcium chloride as coagulant (at varying concentration) to reduce membrane fouling while enhancing NOM removal. Membrane cleaning efficiency through calcium-EDTA chelation which disintegrates the fouling layers was explored. RO fouling was performed with sodium alginate solutions and lake water. The fouled membranes were soaked in 0.1 ​mM EDTA (1 ​h) and backwashed with water to remove the fouling layer. Alginate fouling was worsened (45–85 ​%) by increase in calcium concentration up to 5 ​mM but lessened at > 5 ​mM calcium concentration (35–15 ​%). Similar observations were made when filtering lake water, except that lesser fouling was observed at calcium concentrations greater than 15 ​mM. Membrane soaking in EDTA enhanced cleaning efficiency leading to over 90 ​% flux recovery for both alginate and late water. However, prolonged membrane exposure to 10 ​mM calcium resulted in slight decline in membrane salt rejection (<2 ​% change) and tensile stress (1.3–1.1 ​N/mm2), while the membrane flux increased (<3 ​% change). Finally, NOM removal improved with calcium addition (up to 90 ​%) – key in reducing potential formation of disinfection by-products due to addition of disinfection agents. The proposed use of calcium as a common coagulant/chelating agent for fouling mitigation/remediation during advanced membrane filtration has a potential for wider application and commercialization.